GLOBAL TIME SCALE AND REGIONAL STRATIGRAPHIC REFERENCE SCALES OF CENTRAL AND WEST EUROPE, EAST EUROPE, TETHYS, SOUTH CHINA, AND NORTH AMERICA AS USED IN THE DEVONIAN-CARBONIFEROUS-PERMIAN CORRELATION CHART 2003 (DCP 2003) - Menning M.; Alekseev A.S.; Chuvashov B.I.; Davydov V.I.; Devuyst F.-X.; Forke H.C.; Grunt T.A.; Hance L.; Heckel P.H.; Izokh N.G.; Jin Y.-G.; Jones P.J.; et al. (My University, 2006)
The boundaries of the Devonian, Carboniferous, and Permian stages of the Global Stratigraphic Reference Scale (abbreviated to Global Stratigraphic Scale-GSS) are described in relation to the biostratigraphic and/or lithostratigraphic units of the Regional Stratigraphic Reference Scales (abbreviated to Regional Stratigraphic Scales-RSS) of Central and West Europe, East Europe, Tethys, South China (eastern Tethys), and North America. In their type regions the boundaries of GSS units rarely coincide with those of homonymous RSS units. Moreover, the definitions of some RSS units have changed several times over the last decades, and subsequent misunderstanding of the stratigraphical significance of these changes has often introduced errors into proposed global correlation charts. The stratigraphic framework proposed in our global Devonian-Carboniferous-Permian Correlation Chart 2003 [DCP 2003 (Devonian-Carboniferous-Permian Correlation Chart 2003, Menning, M., Schneider, J. W., Alekseev, A. S., Amon, E. O., Becker, G., von Bitter, P. H., Boardman, D. R., Bogoslovskaya, M., Braun, A., Brocke, R., Chernykh, V., Chuvashov, B. I., Clayton, G., Dusar, M., Davydov, V. I., Dybova-Jachowicz, S., Forke, H. C., Gibling, M., Gilmour, E. H., Goretzki, J., Grunt, T. A., Hance, L., Heckel, P. H., Izokh, N. G., Jansen, U., Jin Y.-G., Jones, P., Käding, K.-Ch., Kerp, H., Kiersnowski, H., Klets, A., Klug, Ch., Korn, D., Kossovaya, O., Kotlyar, G. V., Kozur, H. W., Laveine, J.-P., Martens, Th., Nemyrovska, T. I., Nigmadganov, A. I., Paech, H.-J., Peryt, T. M., Rohn, R., Roscher, M., Rubidge, B., Schiappa, T. A., Schindler, E., Skompski, S., Ueno, K., Utting, J., Vdovenko, M. V., Villa, E., Voigt, S., Wahlman, G. P., Wardlaw, B. R., Warrington, G., Weddige, K., Werneburg, R., Weyer, D., Wilde, V., Winkler Prins, C. F., Work, D. M., 2004). Abschlußkolloquium DFG-Schwerpunktprogramm 1054: Evolution des Systems Erde während des jüngeren Paläozoikums im Spiegel der Sedimentgeochemie. Abstracts Univ. Erlangen, Germany, 2004, p. 43.] (herein abbreviated to DCP 2003, and cited as DCP, 2003 in references) is an attempt to reduce these errors. The DCP 2003 is the stratigraphic base for Project 1054 of the Deutsche Forschungsgemeinschaft (DFG) "The evolution of the Late Palaeozoic in the light of sedimentary geochemistry". This composite time scale has been carefully balanced, as far as data allows, to remove unnecessary, artificial compression and expansion of time intervals, biozonations and depositional events. The ages selected in DCP 2003 are markedly different to those in the Geologic Time Scale 1989 [GTS 1989 (Harland, W.B., Armstrong, R.L., Cox, A.V., Craig, L.E., Smith, A.G., Smith, D.G., 1990). A geologic time scale 1989. Cambridge Univ. Press, Cambridge.; Harland, W.B., Armstrong, R.L., Cox, A.V., Craig, L.E., Smith, A.G., Smith, D.G., 1990. A geologic time scale 1989. Cambridge Univ. Press, Cambridge, pp. 1-263.] and in Gradstein and Ogg [Gradstein, F.M., Ogg, J., 1996. A Phanerozoic time scale. Episodes 19 (1/2), 3-4, insert.), whereas they are closer to those of the Geologic Time Scale 2004 [GTS 2004; Gradstein, F.M., Ogg, J.G., Smith, A.G., 2004. A Geologic Time Scale 2004. Cambridge Univ. Press, Cambridge, pp. 1-589.]. Mostly, the ages are rounded to the nearest 0.5 Ma in order to avoid estimates of questionable accuracy, whereas ages of 0.1 Ma in the GTS 2004 and their error bars of ± 0.4 Ma to ± 2.8 Ma for the Devonian to Permian stage boundaries suggest an improved accuracy. In contrast, in the DCP 2003 questionable ages and positions of stratigraphic boundaries are marked by arrows. © 2006 Elsevier B.V. All rights reserved.
Keywords: ASIA; CARBONIFEROUS; DEVONIAN; EUROPE; MARINE-TERRESTRIAL CORRELATIONS; NORTH AMERICA; PERMIAN; TIME SCALE; Paleozoic::Carboniferous; Палеозой::Каменноугольная; Paleozoic::Devonian; Палеозой::Девонская; Paleozoic::Permian; Палеозой::Пермская